THE DEVELOPMENT OF POP MUSIC ART IN UZBEKISTAN: A CULTURAL AND TECHNOLOGICAL EVOLUTION - Ziyodov O. (Bright Mind Publishing, 2025)
The art of pop music in Uzbekistan has been significantly developing in recent years. This progress has led to the enrichment of pop music performance and the expansion of musical genres in the country. The uniqueness of pop music and its role in Uzbek culture are widely discussed today. The harmony between international influences and national traditions, as well as innovations in music and culture, has contributed to the growth of pop music in Uzbekistan. Major festivals, music competitions, and the impact of modern technologies have determined the future direction of Uzbek pop music. This annotation provides information about the key factors influencing the development of pop music in Uzbekistan, its rise, and its place in the world.
Keywords: Uzbekistan, pop music, musical art, development, performance, culture, international influences, modern technologies, festivals, music competitions.